A Rapid‐Ab/Desorption and Portable Photothermal MIL‐101(Cr) Nanofibrous Composite Membrane Fabricated by Spray‐Electrospinning for Atmosphere Water Harvesting. Issue 1 (26th January 2022) - Li, Ailin; Xiong, Jian; Liu, Ye; Wang, Liming; Qin, Xiaohong; Yu, Jianyong
Abstract : MIL‐101(Cr) is a promising moisture absorbent for solar‐driven water harvesting from moisture to tackle the worldwide water shortage issue. However, the MIL‐101(Cr) powder suffers from a long ab/desorption cycle due to the crystal aggregation caused by its inherent powder properties. Here, we demonstrate a MIL‐101(Cr) nanofibrous composite membrane with a nanofibrous matrix where MIL‐101(Cr) is monodisperse in the 3D porous nanofibrous matrix through a simple spray‐electrospinning strategy. The continuous porous nanofibrous matrix not only offers sufficient sites for MIL‐101(Cr) loading but also provides rapid moisture transport channels, resulting in a super‐rapid ab/desorption duration of 50 min (including an absorption process for 40 min and a desorption process for 10 min) and multicycle daily water production of 15.9 L kg −1 d −1 . Besides, the MIL‐101(Cr) nanofibrous composite membrane establishes a high solar absorption of 92.8%, and excellent photothermal conversion with the surface temperature of 70.7 °C under one‐sun irradiation. In addition, the MIL‐101(Cr) nanofibrous composite membrane shows excellent potential for practical application due to its flexibility, portability, and use stability. This work provides a new perspective of shortening MOF ab/desorption duration by introducing a porous nanofibrous matrix to improve the specific water production for the solar‐driven ab/desorption water harvesting technique. Abstract : A MIL‐101(Cr) composite membrane where MIL‐101(Cr) is monodisperse in the 3D porous nanofibrous matrix was demonstrated through a simple spray‐electrospinning strategy. The continuous porous nanofibrous matrix not only offers sufficient sites for MIL‐101(Cr) loading but also provides rapid moisture transport channels, resulting in a super‐rapid ab/desorption duration of 50 min and multicycle daily water production of 15.9 L kg −1 d −1 .